Doing Business in Afghanistan 2017 - World Bank Group (World Bank, Washington, DC, 2017)
Doing Business in Afghanistan 2017 is the first report of the subnational Doing Business series in Afghanistan. It measures business regulations and their enforcement in five provinces. The provinces are compared against each other, and with 189 other economies worldwide. The objective of the study is to gain a broader understanding of the business regulatory environment across Afghanistan as well as to provide good-practice examples and reform recommendations to help guide policy at the national and subnational levels. The study focuses on indicator sets that measure the complexity and cost of regulatory processes affecting four stages in the life of a small to medium-size domestic firm—starting a business, dealing with construction permits, getting electricity and registering property. These four indicator sets were selected because they relate to areas of business regulation in which implementation of the common legal and regulatory framework differs across locations—because of differences in local interpretations of the law and in the resources and efficiency of local agencies responsible for administering regulation. While highly centralized line ministries hold the direct formal authority for the delivery of most services in the provinces, cutting across this system are the provincial governors, who have little formal responsibility for service delivery but wield local power and authority. The report also includes a gender dimension, with the indicator sets for starting a business and registering property expanded to account for gender-differentiated practices.